Optical and mid-infrared neon abundance determinations in star-forming regions - Dors Junior, Oli L. (2013)
We have used observational spectroscopic data of star-forming regions compiled from the literature and photoionization models to analyse the neon ionic abundances obtained using both optical and mid-infrared emission lines. Comparing Ne++/H+ ionic abundances from distinct methods, we have found that, on average, the abundances obtained via infrared emission lines are higher than those obtained via optical lines, by a factor of 4. Photoionization models with abundance variations along the radius of the hypothetical nebula provide a possible explanation for a large part of the difference between ionic abundances via optical and infrared emission lines. The ionization correction factor (ICF) for the neon is obtained from direct determinations of ionic fractions using infrared emission lines. We derive a constant Ne/O ratio (log Ne/O ≈ -0.70) for a large range of metallicities, independently of the ICF used to compute the neon total abundance.